Finisher lamb growth and rumen fermentation responses to the plane of nutrition and naturally occurring coccidiosis - Sujani, Sathya; dos Reis, Barbara R.; Ellett, Mark D.; Schramm, Holly H.; Helm, Emma T.; White, Robin R. (Frontiers in Veterinary Science, 2023)
The objective of the present study was to investigate the interaction of plane of nutrition and naturally occurring coccidiosis on finisher lamb growth performance, FAMACHA score, and rumen volatile fatty acid profile. The study included 30 Suffolk, Dorset or Suffolk x Dorset lambs and were divided into 2 groups based on their initial body weight and assigned to 2 feeding groups. Lambs with naturally occurring coccidiosis and healthy lambs were present in both feeding groups making a 2x2 factorial arrangement of treatments, a) high plane of nutrition (HPN) lambs with no clinical coccidiosis diagnosis (HPNH), b) HPN lambs with clinical coccidiosis (HPNC), c) low plane of nutrition (LPN) lambs with no clinical coccidiosis diagnosis (LPNH), d) LPN lambs with clinical coccidiosis (LPNC). Body weight and FAMACHA scores were recorded once every 2 weeks. On d 65 of feeding, lambs were slaughtered, and rumen fluid samples were collected and analyzed for volatile fatty acid concentrations. The total and average weight gain were not associated with planes of nutrition, health status, or the interaction. Health status had an impact on FAMACHA© score (P = 0.047) and concentration of isobutyrate (P = 0.037) and tended to affect total VFA (P = 0.085) and acetate (P = 0.071) concentrations. The interaction between the plane of nutrition and the health status tended to affect butyrate concentration (P = 0.058). These data support the conclusion that coccidiosis infection impacted on rumen fermentation in a manner independent of the plane of nutrition.